Prestige over Profit: The Practice of Digital Entrepreneurship among Millennial Generation in Indonesia - Dzillin Jihan; Kustana Kustana (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Digital entrepreneurship has recently become a trend in cyberspace and it is often associated with the millennials who were previously said to be the least entrepreneurial generation. The millennials are digital natives who tend to follow a trend because of globalization which opens up unlimited public spaces. This article aims to examine the motives of the Indonesian millennial generation in doing digital entrepreneurship through qualitative research methods and Jean Baudrillard's post-modern theory approach. The required data were collected through interview and observation methods. This article argues that the main motive of Indonesian millennials in digital entrepreneurship is not profit-seeking, but rather prestige-seeking by following trends on social media so that digital entrepreneurship develops among millennials. The results of the study show that the tendency of being social media trend followers has encouraged Indonesian millennials to run digital entrepreneurship. The millennials tried to follow the trend of digital entrepreneurship to express their identities in the public sphere to create a good image of themselves. By doing so, they expected to be considered prestigious members of digital society with higher social status.